Pemanfaatan TOR BISKUIT sebagai MP-ASI pada Bayi Stunting Usia 12-18 Bulan - Ivan Elisabeth Purba; Donal Nababan; Siska Evi Martina; Junius Dermawan Zebua (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
There is a serious problem of stunting in Indonesia, specifically stunted growth due to malnutrition during a child's growth period. This condition not only affects physical health but also affects cognitive, emotional, and mental aspects. Therefore, specific measures are needed to overcome this problem. With the aim of overcoming developmental delays, this service explores the potential of the TOR BISCUIT innovation as a Breast Milk Supplement (MP-ASI) for stunted children aged 12-18 months. The service uses a case study approach and combines quantitative and qualitative methods. The service's sample included 77 stunted children who received cookies, and the military also conducted face-to-face interviews with parents in the target service area, specifically the Belawan region. This undertaking not only aims to explore the effectiveness of TOR BISCUIT Innovation as MP-ASI but also aims to provide concrete and effective solutions to tackle the problem of stunting in Indonesia. By applying a combination of quantitative and qualitative approaches, it is hoped that this service can provide a comprehensive picture of the impact of providing these biscuits on growth and development of stunted children. It is hoped that the results of this service can provide a solid basis for governments, health organizations and communities to implement effective and sustainable interventions to reduce stunting rates. in Indonesia. In this way, it is hoped that Indonesia's young generation can grow and develop optimally, thereby better contributing to the country's progress.